2 + 3(x -1) = 5( x +4) - 7

Algebra
Tutor: None Selected Time limit: 1 Day

2 + 3(x -1) = 5( x +4) - 7

Oct 1st, 2015

Thank you for the opportunity to help you with your question!

2 + 3(x -1) = 5( x +4) - 7

Open the brackets

2 + 3x -3 = 5x + 20 -7

Collect like terms together

3x+2-3=5x+13

3x-1=5x+13

3x-5x=13+1

-2x=14

x=-14/2=-7

Please let me know if you need any clarification. I'm always happy to answer your questions.
Oct 1st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 1st, 2015
...
Oct 1st, 2015
Feb 25th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer